Biomaterials’ enhancement of immunotherapy for breast cancer by targeting functional cells in the tumor micro-environment - Santerre, J. Paul; Yang, Yangyang; Du, Ziwei (Frontiers in Immunology, 2024)
Immunotherapy for breast cancer is now being considered clinically, and more recently, the number of investigations aimed specifically at nano-biomaterials-assisted immunotherapy for breast cancer treatment is growing. Alterations of the breast cancer micro-environment can play a critical role in anti-tumor immunity and cancer development, progression and metastasis. The improvement and rearrangement of tumor micro-environment (TME) may enhance the permeability of anti-tumor drugs. Therefore, targeting the TME is also an ideal and promising option during the selection of effective nano-biomaterial-based immuno-therapeutic strategies excepted for targeting intrinsic resistant mechanisms of the breast tumor. Although nano-biomaterials designed to specifically release loaded anti-tumor drugs in response to tumor hypoxia and low pH conditions have shown promises and the diversity of the TME components also supports a broad targeting potential for anti-tumor drug designs, yet the applications of nano-biomaterials for targeting immunosuppressive cells/immune cells in the TME for improving the breast cancer treating outcomes, have scarcely been addressed in a scientific review. This review provides a thorough discussion for the application of the different forms of nano-biomaterials, as carrier vehicles for breast cancer immunotherapy, targeting specific types of immune cells in the breast tumor microenvironment. In parallel, the paper provides a critical analysis of current advances/challenges with leading nano-biomaterial-mediated breast cancer immunotherapeutic strategies. The current review is timely and important to the cancer research field and will provide a critical tool for nano-biomaterial design and research groups pushing the clinical translation of new nano-biomaterial-based immuno-strategies targeting breast cancer TME, to further open new avenues for the understanding, prevention, diagnosis and treatment of breast cancer, as well as other cancer types.